Analogy between the spectral signature of the jarosite from the pinchollo area in peru and from the meridiani planum on mars and recognition of the mineralization process (2020)
This study tries to establish a comparison between environments hosting the mineral jarosite on Earth and Mars. In order to establish a comparison and possible analogy between the environments of these planets, the objective of this work is to find similarities between the spectral signatures and the mineralization process of the jarosite, a potassium and iron sulphate hydrous mineral, found in both places, and might be a possible signal of the previous water occurrence. Through the processing of images taken from the CRISM, HIRISE and Hyperion databases, looking for the main spots of accumulation of jarosite in the area of Pinchollo geyser in Peru and in craters identified by the rover "Opportunity" in Meridiani Planum. Thanks to the high spectral resolution of the Hyperion sensor, it was possible to recognize some depressive areas near the geyser that show greater presence of materials with a spectral signature similar to that of the reference jarosite taken from Beckman Coulter instrument. On the other hand, the CRISM images suggest a greater abundance of materials with a similar spectral signature of jarosite in areas where erosion and wind transport impact the Martian terrain near to Eagle and Endeavour craters